2018
DOI: 10.1093/mnras/sty1185
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in s-process nucleosynthesis in low-mass stars determined from Monte Carlo variations

Abstract: The main s-process taking place in low mass stars produces about half of the elements heavier than iron. It is therefore very important to determine the importance and impact of nuclear physics uncertainties on this process. We have performed extensive nuclear reaction network calculations using individual and temperature-dependent uncertainties for reactions involving elements heavier than iron, within a Monte Carlo framework. Using this technique, we determined the uncertainty in the main s-process abundance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…Within the multievent model it was possible to evaluate the major uncertainties (both nuclear and due to abundance measurements) affecting the prediction of the s-(r-)abundance distribution. Goriely (1999) concluded that the uncertainties in the ob-served meteoritic abundances and the relevant (n, γ) rates have a significant impact on the predicted s-component of the solar abundance and, consequently, on the derived rabundances, especially concerning the s-dominated nuclei (see also Nishimura et al 2017 andCescutti et al 2018).…”
Section: Determination Of S-and R-abundancesmentioning
confidence: 99%
“…Within the multievent model it was possible to evaluate the major uncertainties (both nuclear and due to abundance measurements) affecting the prediction of the s-(r-)abundance distribution. Goriely (1999) concluded that the uncertainties in the ob-served meteoritic abundances and the relevant (n, γ) rates have a significant impact on the predicted s-component of the solar abundance and, consequently, on the derived rabundances, especially concerning the s-dominated nuclei (see also Nishimura et al 2017 andCescutti et al 2018).…”
Section: Determination Of S-and R-abundancesmentioning
confidence: 99%
“…3. The standard rate set and the assigned uncertainties were the same as previously used in our works (Rauscher et al 2016;Nishimura et al 2017Nishimura et al , 2018Cescutti et al 2018): rates for neutron-, proton-, and α-induced reactions were a combination of theoretical values by Rauscher & Thielemann (2000), supplemented by experimental rates taken from Dillmann et al (2006) and Cyburt et al (2010). Decays and electron captures were taken from a REACLIB file compiled by Freiburghaus & Rauscher (1999) and supplemented by rates from Takahashi & Yokoi (1987) and Goriely (1999) as provided by Aikawa et al (2005) and Xu et al (2013).…”
Section: Nucleosynthesis With Monte Carlo Variationsmentioning
confidence: 99%
“…The trajectories specify the temporal evolution of density and temperature and can be taken from any astrophysical simulation. PizBuin so far was already applied to a number of processes: the γ process in core-collapse supernovae (ccSN) [1], the production of p nuclei in white dwarfs exploding as thermonuclear (type Ia) supernovae (SNIa) [2], the weak s process in massive stars [3], and the main s process in AGB stars [4].…”
Section: Introductionmentioning
confidence: 99%